Low Frequency of Acquired Isoniazid and Rifampicin Resistance in Rifampicin-Susceptible Pulmonary Tuberculosis in a Setting of High HIV-1 Infection and Tuberculosis Coprevalence. (20th July 2017) - Rockwood, Neesha; Sirgel, Frederick; Streicher, Elizabeth; Warren, Robin; Meintjes, Graeme; Wilkinson, Robert J
Summary: In a setting of high tuberculosis and human immunodeficiency virus type 1 infection coprevalence, low prevalence of isoniazid monoresistance, treatment with daily standardized antituberculosis regimens throughout and high uptake of antiretroviral therapy were associated with low frequency of acquired drug resistance. Prevention of transmitted resistance should be prioritized. In a setting of high tuberculosis and human immunodeficiency virus type 1 infection coprevalence, low prevalence of isoniazid monoresistance, daily treatment with standardized antituberculosis regimens throughout the study period, and high uptake of antiretroviral therapy were associated with low frequency of acquired drug resistance. Prevention of transmitted resistance should be prioritized. Abstract: Background: We estimated the incidence of acquired isoniazid and rifampicin resistance in rifampicin-susceptible tuberculosis in a setting of high human immunodeficiency virus type 1 (HIV-1) infection and tuberculosis coprevalence. Methods: GeneXpert MTB/RIF–confirmed patients with rifampicin-susceptible tuberculosis were recruited at antituberculosis treatment initiation in Khayelitsha, South Africa. Liquid culture and adherence assessment were performed at 2 and 5–6 months. MTBDRplus was performed on mycobacteria-positive cultures to ascertain acquired drug resistance (ADR). Spoligotyping and whole-genome sequencing were performed to ascertain homogeneity between baseline isolates and isolates with ADR. Baseline isolates were retrospectively tested for isoniazid monoresistance. An electronic database review was performed to ascertain tuberculosis recurrences. Results: A total of 306 participants (62% with HIV-1 coinfection, of whom 71% received antiretroviral therapy) were recruited. Ascertainment of outcomes was complete for 284 participants. Five acquired a resistant Mycobacterium tuberculosis strain during or subsequent to treatment. One strain was confirmed to have ADR, 2 were confirmed as causing exogenous reinfection, and 2 were unrecoverable for genotyping. Incident ADR was estimated to have ranged from 0.3% (95% confidence interval [CI], .1%–1.9%; 1 of 284 participants) to 1% (95% CI, .2%–3%; 3 of 284 participants). Seventeen of 279 baseline isolates (6.1%; 95% CI, 3.6%–9.6%) had isoniazid monoresistance (13 of 17 had an inhA promoter mutation), but 0 of 17 had amplified resistance. Conclusions: Treatment with standardized antituberculosis regimens dosed daily throughout, high uptake of antiretroviral therapy, and low prevalence of isoniazid monoresistance were associated with a low frequency of ADR.